Impact of Investment Knowledge, Financial Literacy, and Minimum Capital Requirements on Student Stock Investment Interest - Mulyani, Ni Putu; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2024)
This research investigates the effects of investment knowledge, financial literacy, and minimum capital requirements on students' enthusiasm for stock investments. It focuses on students from the 2020 and 2021 Bachelor of Accounting classes at the Faculty of Economics and Business, Udayana University. A purposive sampling method was employed to choose 250 participants. The analysis utilized multiple linear regression. Results show that investment knowledge, financial literacy, and minimum capital requirements significantly enhance students' interest in stock investments, supporting the Theory of Planned Behavior's relevance in understanding investment-related student behaviors. Keywords: Investment Knowledge, Financial Literacy, Minimum capital requirements, Interest In Stock Investment